Protocol for Sonogashira coupling of alkynes and aryl halides via nickel catalysis - Hui Chen; Zhenkang Ai; Xuebin Liao (STAR Protocols, 2024)
Summary: Alkynes are widely present in natural products and pharmaceutical compounds. Here, we present a protocol for nickel-catalyzed cross-coupling of terminal alkynes with aryl iodides or bromides for constructing a C(sp2)-C(sp) bond. We describe steps for reagent preparation, reaction setup, purification process, and product characterization. We also detail procedures for obtaining a single crystal of 6-(phenylethynyl)-1-(phenylsulfonyl)-1H-indole (3b). The application of this protocol is limited to aryl bromide and iodide.For complete details on the use and execution of this protocol, please refer to Chen et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.